The Current Mental Health of Healthcare Workers 3 Years After the Start of the Pandemic: The Relationship Between Coping Strategies and Indices of Mental Health - Serrano-Ibáñez, Elena R.; De la Vega-Castelo, Ariadna; Varela, Carmen; Montero-Matellanes, M. Mikel; Gómez-Pulido, Almudena (Sage Journals, 2024)
Healthcare workers have been a vulnerable group during the pandemic. Even today, they continue to deal with the virus and its consequences. Such sustained stress over time has led to the development of mental health problems that may still be present in this population. These may be related to the coping strategies that are being implemented to manage this situation. This study aimed to examine the mental health of health professionals after the end of the acute phase of the pandemic and investigate which coping strategies predicted levels of stress, anxiety, depression, and burnout. A total of 285 healthcare workers were assessed. Descriptive and multiple regression analyses were performed. The result showed (a) levels of mild-to-moderate depressive symptomatology, moderate levels of stress and anxiety symptomatology, and a medium level of burnout; and (b) acceptance, behavioral disengagement, negation, substance use, and active coping as the strategies most implicated in this symptomatology. Interventions that help health professionals to develop adaptive coping strategies, thus avoiding or reducing the development of psychological symptoms, should be implemented.
Keywords: healthcare workers; depression; anxiety; stress; burnout; coping strategies; Scopus